2020
DOI: 10.21203/rs.3.rs-20826/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor-suppressor miRNA-27b-5p regulates the growth and metastatic behaviors of ovarian carcinoma cells by targeting CXCL1

Abstract: BackgroundMicroRNAs (miRNAs) play crucial functions in the progression of ovarian cancer. MicroRNA-27b-5p (miR-27b-5p) has been identified as a cancer-associated miRNA. Nevertheless, the expression profile of miR-27b-5p and its functions in ovarian cancer are unexplored.MethodsqRT-PCR and western blot analysis were used to detect the levels of miR-27b-5p and C-X-C motif chemokine ligand 1 (CXCL1). The impact of miR-27b-5p on ovarian cancer cells proliferation, migration and invasion in vitro were investigated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Additionally, another study examining a total of 2573 patients also suggested that overexpression of miR-92a serves as an unfavorable prognostic indicator in LUAD patients [35]. To our knowledge, miR-27b-5p had been reported as a tumor suppressor in ovarian carcinoma and oral cancer [20,36], but it is highly expressed in gastric adenocarcinoma and may play a positive role in tumorigenesis and development [37]. However, regrettably, no study has reported the relationship between Evidence-Based Complementary and Alternative Medicine miR-27b-5p and lung cancer.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, another study examining a total of 2573 patients also suggested that overexpression of miR-92a serves as an unfavorable prognostic indicator in LUAD patients [35]. To our knowledge, miR-27b-5p had been reported as a tumor suppressor in ovarian carcinoma and oral cancer [20,36], but it is highly expressed in gastric adenocarcinoma and may play a positive role in tumorigenesis and development [37]. However, regrettably, no study has reported the relationship between Evidence-Based Complementary and Alternative Medicine miR-27b-5p and lung cancer.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, researchers have demonstrated that chemokines can affect progression of several tumors such as lung cancer, bladder As CXC chemokines and their receptors may be potentially used in molecular targeting of cancers, accumulating researches have focused on CXC chemokine family and their receptors in ovarian cancer. For instance, researchers found that tumor-suppressor miRNA-27b-5p regulated the growth and metastatic behaviors of ovarian carcinoma cells by targeting CXCL1 [27]. CXCL4 insufficiency was involved in specific inflammatory microenvironment of ovarian cancers arising in endometriosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-574-3p has been indicated to inhibit the malignant behavior of liver cancer cells via interacting with disintegrin and metalloproteinase domain-containing protein 28 (17). Moreover, miR-27b-5p has been reported to repress the growth and metastasis of ovarian carcinoma cells by targeting C-X-C motif chemokine 1 (18). In addition, the suppressive effect of miRNAs, such as miR-188-5p and miR-1271, on the progression of HCC has also been demonstrated in previous studies (19,20).…”
Section: Introductionmentioning
confidence: 99%